INTESTATE SUCCESSION LAW AND ITS EFFECTS ON FAMILY RELATIONSHIP IN ASANTE, THE CASE OF WIDOWERS - Aboagye, Samuel Kwadwo (LexCult: revista eletrônica de direito e humanidades; v. 9 n. 1 (2025): Cultura, Política e Justiça, 2024)
The research investigated the effects of the application of the intestate succession law (PNDC Law 111) on family relationships, in the event of the death of Asante women. Five widowers who had applied the law in distributing the properties of their deceased wives were purposively sampled from different locations in Asante to constitute the target population, and in-depth interviews through an interviewers’ guide were conducted with them and their family members. The study revealed widespread knowledge and application of the law. However, it appeared that the application of the law had marred relationships not only between widowers and their children – both biological and step-children – but also between widowers and members of the deceased’s lineage. In some cases, such strained relationships were characterized by deep-seated animosity, insults, quarrels and bitterness as a result of the application of the law. In other cases, cordial relationships existed between widowers, children and the deceased’s family members. Recommendations from the study, among other things, were that couples should register properties they acquire in the name of both partners, they should learn not only to make wills but also separate family properties from their personal ones.